Pengaruh ekstrak rimpang Cyperus rotundus L. terhadap pertumbuhan jamur Botryodiplodia theobromae penyebab penyakit blendok pada jeruk secara in vitro - Maryana, Maryana; Dirmawati, Suskandini Ratih; Wibowo, Lestari; Efri, Efri (Universitas Lampung, 2025)
Bleeding disease in tangerine plants is caused by the fungus Botryodiplodia theobromae. This study aimed to determine the effect of Cyperus rotundus L. extract on the growth of B. theobromae mycelia and spores in vitro, and to determine the best concentration of C. rotundus extract in inhibiting the growth of the fungus. The study was conducted using a Completely Randomized Design (CRD) consisting of 7 treatments, namely C. rotundus extract concentrations of 0.0% (control), 0.1%, 0.2%, 0.3%, 0.4%, and 0.5%, as well as a fungicide treatment containing the active ingredient carbendazim 0.1%. The observed variable was fungal growth measured by colony diameter. The results showed that the treatment of sedge rhizome extract was able to suppress the development of B. theobromae fungal colonies. This nutmeg rhizome extract has the potential to be developed as a botanical pesticide to control B. theobromae fungus, and a concentration of 0.5% nutmeg rhizome extract has the highest inhibitory power against the growth of B. theobromae fungus, namely 56%.